ANALISIS KETERKAITAN STORE IMAGE, CUSTOMER SATISFACTION DAN REPURCHASE INTENTION (SURVEI PADA PELANGGAN SJS PLAZA) - Elsa Felina Effendi, Eri Besra (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
This research aims to analyze the relationships of store image, customer satisfaction and repurchase intention  at SJS Plaza. The number of samples are 195 respondents. The validity test of sample was done with loading factor test and the average variance extracted (AVE) value, while the reliability used internal consistency test based on the composite reliability value. The loading factor test and the value of the AVE showed valid values. The internal consistency test had composite reliability value which meet the criteria. Based on the test result, all indicator variable statements have met the criteria of validity and reliability. The hypothesis test with SmartPLS 3.0 show that store image had positive effect and significant towards customer satisfaction, customer satisfaction had positive effect and significant towards repurchase intention and store image had positive effect and not significant towards repurchase intention directly. But it has a positive and significant effect if customer satisfaction mediates between store image and repurchase intention.